A genomic approach to coral-dinoflagellate symbiosis: studies of Acropora digitifera and Symbiodinium minutum - Shinzato, Chuya; Mungpakdee, Sutada; Satoh, Nori; Shoguchi, Eiichi (Frontiers in Microbiology, 2014)
Far more intimate knowledge of scleractinian coral biology is essential in order to understand how diverse coral-symbiont endosymbioses have been established. In particular, molecular and cellular mechanisms enabling the establishment and maintenance of obligate endosymbiosis with photosynthetic dinoflagellates require further clarification. By extension, such understanding may also shed light upon environmental conditions that promote the collapse of this mutualism. Genomic data undergird studies of all symbiotic processes. Here we review recent genomic data derived from the scleractinian coral, Acropora digitifera, and the endosymbiotic dinoflagellate, Symbiodinium minutum. We discuss Acropora genes involved in calcification, embryonic development, innate immunity, apoptosis, autophagy, UV resistance, fluorescence, photoreceptors, circadian clocks, etc. We also detail gene loss in amino acid metabolism that may explain at least part of the Acropora stress-response. Characteristic features of the Symbiodinium genome are also reviewed, focusing on the expansion of certain gene families, the molecular basis for permanently condensed chromatin, unique spliceosomal splicing, and unusual gene arrangement. Salient features of the Symbiodinium plastid and mitochondrial genomes are also illuminated. Although many questions regarding these interdependent genomes remain, we summarize information necessary for future studies of coral-dinoflagellate endosymbiosis.